Building social capital from sport event participation: An exploration of the social impacts of participatory sport events on the community. Issue 5 (November 2018) - Zhou, Ran; Kaplanidou, Kyriaki
Highlights: Active participation in running events can foster rich bonding capital. The bridging and linking capital differ across event types and participant types. Social capital from event participation can lead to four types of positive outcomes. Benefits for the running and broader community were discussed in light of social capital outcomes. Abstract: Participatory sport events have the potential to generate substantial social value in the local community. One important social benefit of such sport events is the development of social capital. However, little is known about the development and outcomes of social capital in the context of participatory sport events, such as running events. Taking a qualitative approach, the authors explored the social capital building among active participants in running events. The findings revealed that bonding capital is developed by all participants in the study while the bridging and linking capital varies by event type and involvement level. Moreover, four positive outcomes of social capital were identified: supportive attitude and behaviors, positive influence on others, prosocial behaviors, and increased everyday socializations. By generating these positive outcomes among the participants of this study, social capital has the potential to contribute to the community development and well-being. This study provides insights as to how social capital that stems from sport event participation can lead to the development of community in the long term. Suggestions are made for future research to test the relationships between social capital, its outcomes, and community development and well-being.